In the public's interest: evictions, citizenship, and inequality in contemporary Delhi - Bhan, Gautam (Geographies of justice and social transformation, 2016)
Introduction: "how did we get here?" -- Planned illegalities : the production of housing in Delhi 1947-2010 -- Planned development and/as crisis : evictions and the politics of governance in contemporary Delhi -- Unmaking citizens : spatial illegality, urban citizenship and the challenges for inclusive politics -- "You can't just walk into a court" : notes on the judicialisation of resistance -- Concluding provocations : inquiries from the South -- Notes -- References -- Index